Avaliaç\~ao da eficiência técnica dos países nos Jogos Olímpicos de Pequim - 2008 - Alexandre Marinho; Simone de Souza Cardoso; Vivian Vicente de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– We rank the participant nations in the Beijing 2008 Olympic Games according to their technical efficiency. Usually they are ranked in accordance with the number of medals they have won and no resources available are considered. In order to evaluate the relative performance of the countries, we used an output oriented version of Data Envelopment Analysis (DEA). We consider three inputs (GDP, population and life expectancy at birth) and different combinations of three outputs (number of gold, silver and bronze medals won).
Keywords: C61; C67; F53; Z00; 330